Emerging technologies in NDT proceedings of the 2nd International Conference on Emerging Technologies in NDT, Athens, Greece, 24-26 May 1999 - Hemelrijck, Danny van; Philippidis, Theodore (A.A. Balkeman, 2000)
This volume contains the papers presented at the 2nd International Conference entitled: "Emerging Technologies in NDT" which was held in Athens, Greece, May 24-26, 1999. This work covers frequently used non-destructive testing methods and introduces innovative ideas in the field. The title also focuses on visual and optical inspection, acoustic emission and ultrasonics as well as a range of other closely related topics. More than 50 papers were presented at the conferecne by invited and distinguished researchers from all over the world. This volume forms a valuable record of important contributions to the relevant literature. It contains not only the most up-to-date technology developments but provides also information regarding emerging NDT techniques/technologies and their potential applications in the field. The book covers frequently used NDT methods and introduces new and innovative ideas. Focussing on visual and optical inspection, acoustic emission, ultrasonics, nonlinear ultrasonics, infrared methods, X-ray radiography, special techniques, material characterisation, NDT of civil engineering structures, inspection of pipes and reliability and validation this volume will be a great boon to engineers, researchers, quality control managers, as well as teachers and graduate students in the field.